Transcriptional Regulation of the p53 Tumor Suppressor Gene in S-Phase of the Cell-Cycle and the Cellular Response to DNA Damage - David Reisman; Paula Takahashi; Amanda Polson; Kristy Boggs (Biochemistry Research International)
The p53 tumor suppressor induces the transcription of genes that negatively regulate progression of the cell cycle in response to DNA damage or other cellular stressors and thus participates in maintaining genome stability. Numerous studies have demonstrated that p53 transcription is activated before or during early S-phase in cells progressing from G0/G1 into S-phase through the combined action of two DNA-binding factors RBP-Jκ and C/EBPβ-2. Here, we review evidence that this induction occurs to provide available p53 mRNA in order to prepare the cell for DNA damage in S-phase, this ensuring a rapid response to DNA damage before exiting this stage of the cell cycle.